Two-body hadronic decay of K+ in the presence of a circularly polarized laser field. (1st April 2022) - Baouahi, M.; Dahiri, I.; Ouali, M.; Manaut, B.; Benbrik, R.; Taj, S.
Abstract: In this study, we have investigated the two-body hadronic decay of the charged kaon, , in the presence of a laser field with circular polarization. We have derived, by analytical techniques, the laser-assisted decay width and the branching ratio of the charged kaon decay via the two-body hadronic channel. We have also taken into consideration the impressive results obtained for the laser-assisted charged kaon decay via the leptonic mode in order to understand more clearly the effect of the laser field on the quantities related to the charged kaon decay such as the decay width, the branching ratio and lifetime. A precise comparison of the ratios of hadronic-to-muonic decay in the presence of the laser field is made to show that the hadronic mode becomes slightly more important by increasing the laser field intensity.